2004
DOI: 10.1007/s00467-004-1608-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of levamisole treatment in childhood nephrotic syndrome

Abstract: The effects of levamisole treatment on long-term outcome were evaluated in a retrospective study of frequently-relapsing (FRNS, n=15), steroid-dependent (SDNS, n=13), and steroid-resistant (SRNS, n=6) nephrotic syndrome in 34 children (21 boys, 13 girls, mean age 5.0+/-3.4 years) during a 60-month follow-up period. The definition of frequent relapses was > or = 4 relapses per year. The current relapse was treated with prednisolone 60 mg/m2 per day for 4 weeks, then with 40 mg/m2 every other day for 4 weeks, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Limited data exist, however, as to the long-term efficacy of levamisole therapy after its cessation. A recent retrospective study [9] evaluated frequently relapsing steroid-dependent NS in 13 children treated with 2 mg/kg per day of levamisole for a mean duration of 17 months. Among the steroid-dependent children, 6/13 relapsed while on levamisole, but only 2/13 after its cessation, suggesting that levamisole may have a long-lived effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data exist, however, as to the long-term efficacy of levamisole therapy after its cessation. A recent retrospective study [9] evaluated frequently relapsing steroid-dependent NS in 13 children treated with 2 mg/kg per day of levamisole for a mean duration of 17 months. Among the steroid-dependent children, 6/13 relapsed while on levamisole, but only 2/13 after its cessation, suggesting that levamisole may have a long-lived effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior reports focused on levamisole as an effective adjunctive therapy in reducing short-term relapse frequency (RF), limited data exist as to its long-term efficacy. In a recent retrospective study, its steroid-sparing effects were suggested to last for months after its withdrawal [9]. Even more limited data exists as to the effect of levamisole on steroid-induced clinical complications, such as hypertension, or alterations in somatic measures, such as height and weight.…”
Section: Introductionmentioning
confidence: 97%
“…One of the main observations is the reduced 19,20 interleukin-2 (IL-2) production .Some studies have suggested that minimal change nephrotic syndrome (MCNS) is a T helper 2-dominated (Th2) disease, having observed higher levels of serum interleukin-13 (IL-13) Several studies suggested LEV as the first choice of non-steroidal immunosuppressive agent to achieve less frequent relapses and longer sustained remission in children with FRNS or SDNS, in addition to the decrease 23,24 of steroid-related side effects . Significant reduction of both relapse rate and cumulative steroid dose by LEV in SDNS and FRNS patients was reported in the studies of 25,10,11 Sumegi, Madani and Al-Saran . In a later study by Boyer et al LEV had the additional benefits of normalized blood pressure in hypertensive patients and improved height velocity, even after cessation of LEV No literature-based firm recommendations can be made on how prednisolone should be withdrawn during LEV therapy in order to minimise the risk of relapse.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, when commencing on LEV, all patients should be warned about this potential side-effect and should be advised to stop the drug and report immediately. Neutropenia and liver toxicity have been reported in NS patients using LEV 17,18 . However, neutropenia, anaemia or liver toxicity were not observed in the present study.…”
Section: Discussionmentioning
confidence: 99%